China’s Environmental Protection in the New Era from the Perspective of Eco-civilization Construction - Huan, Qingzhi (Problemy Ekorozwoju, 2020)
Under a particular context of China’ eco-civilization construction in the New Era after the 18th national congress of CPC, an interesting question is that the discourse of socialist eco-civilization and its practice can to what an extent reshape or change the relationship among eco-capital, green technology and public participation in achieving a better environmental governance. A field-study in Fuzhou City, Jiangxi Province, shows clearly that there are both great hope for a radical reconstruction and multitudinous difficulties and challenges in front of the pioneering Green enterprises and the pilot areas of eco-civilization construction.